Brain and Nasal Cavity Anatomy of the Cynomolgus Monkey: Species Differences from the Viewpoint of Direct Delivery from the Nose to the Brain - Toshiyasu Sakane; Sachi Okabayashi; Shunsuke Kimura; Daisuke Inoue; Akiko Tanaka; Tomoyuki Furubayashi (MDPI AG, 2020)
Based on structural data on the nasal cavity and brain of the cynomolgus monkey, species differences in the olfactory bulb and cribriform plate were discussed from the viewpoint of direct delivery from the nose to the brain. Structural 3D data on the cynomolgus monkey skull were obtained using X-ray computed tomography. The dimensions of the nasal cavity of the cynomolgus monkey were 5 mm width × 20 mm height × 60 mm depth. The nasal cavity was very narrow and the olfactory region was far from the nostrils, similar to rats and humans. The weight and size of the monkey brain were 70 g and 55 mm width × 40 mm height × 70 mm depth. The olfactory bulb of monkeys is plate-like, while that of humans and rats is bulbar, suggesting that the olfactory area connected with the brain of monkeys is narrow. Although the structure of the monkey nasal cavity is similar to that of humans, the size and shape of the olfactory bulb are different, which is likely to result in low estimation of direct delivery from the nose to the brain in monkeys.